Malaria preventive measures used by parents of under five years’ children in Ibadan Urban Markets, Nigeria. (2019)
Malaria remains a major public health issue, especially among children in Nigeria. Children are an important group that should be targeted for malaria control. This study, therefore, examined the contextual interpretation and understanding of malaria, existing means of malaria prevention, treatment, and acceptability of chemoprevention among parents, guardians and grandparents of under-5 years children in Ibadan, Nigeria. The study employed qualitative methodology, through the use of observation and in-depth interviews. Two popular markets were purposively selected for the study. In all, 32 in-depth interviews were conducted. Data were coded and sorted with Atlas-ti, and subjected to content analysis. All respondents identified that malaria is caused and spread by the bite of infected mosquitos. Malaria preventive strategies used by parents in Ibadan includes use of long lasting insecticide treated net (LLIN), insecticides, insect repellant cream and herbal malaria mixture (agumu iba) used as prophylaxis. All informants mentioned frequent indoor use of either otapiapia, (a mixture of carbide, gammaline 20 organochloride insecticide, and diesel) and undiluted Sniper (a DDVP chemical family, 2, 2-dichloro vinyl dimethyl phosphate, an outdoor insecticide/miticide that should be diluted with water when used for outside fumigation) as an effective means to preventing mosquito/malaria. All were accepting of the introduction of new ways of preventing malaria such as chemo-preventive malaria drugs for children. The study showed that there is urgent need for awareness campaign on the harmful effects of DDVP chemical family misuse in Ibadan.